The Mediation Effect of Price to Book Value on Financial Ratio to Stock Return - Almuzayyad; Guntur Kusuma Wardana (Universitas Islam Negeri Alauddin Makassar, 2025)
Stock returns are main indicators used by investors to assess the performance of a stock, including those of Islamic financial institutions listed on the Indonesia Stock Exchange (IDX). Stock returns can be influenced by financial ratios such as ROA, DER, CR, TATO, and EPS. This study aims to determine the effect of ROA, DER, CR, TATO, and EPS on stock returns through PBV in Islamic financial institutions listed on the IDX for the period 2020-2024. This study uses a quantitative method. The population in this study consists of 59 companies, including 4 Islamic banks and 55 Islamic insurance companies, using purposive sampling techniques that produced 9 samples. This study used secondary data sourced from quarterly reports Islamic financial institutions listed on the IDX for the period 2020-2024. The results show that PBV is unable to mediate the effect of ROA, DER, CR, TATO, and EPS on the stock returns of Islamic financial institutions listed on the IDX for the period 2020-2024. However, the results of testing the hypothesis of direct influence on stock returns show that DER, CR, TATO, and EPS have a significant effect on stock returns. Meanwhile, ROA does not have a significant effect on stock returns.